Pendampingan Penggunaan Aplikasi Terintegrasi dalam Menilai Kinerja Keuangan UMKM Pekalongan secara Efektif - Fatah, Khoirul; Purwanto, Teguh (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
Effective financial management is essential for the sustainability and growth of small and medium enterprises (SMEs). In today’s digital era, financial technology plays a crucial role for SMEs to remain competitive in a dynamic market. However, many SMEs, such as Daster Pekalongan (Deka Collection), still rely on conventional, manual financial recording, leading to inefficiencies and delayed decision-making processes. This community service project was designed to support Deka Collection in adopting an integrated financial application to improve financial literacy and enable accurate financial management. The method included structured steps: needs analysis, training module development, hands-on application training, field support, and evaluation. Through this approach, Deka Collection gained practical skills in cash flow management, report generation, and real-time transaction monitoring across e-commerce platforms. Post-implementation evaluations revealed improved efficiency, with time spent on financial recording halving from 10 hours to 5 hours per month, and error rates dropping from 15% to 3%. These outcomes demonstrate the positive impact of technology adoption in enhancing SME financial management, enabling more effective decision-making and greater market responsiveness. This initiative highlights the role of digital tools in bolstering business sustainability and economic resilience at the local level.